MIRERC 032/2025: An academic course by the University of Chicago(Harris School) and Busara Center: : Behavioral Experiments in International Development: From Theory to Practice in Nairobi, Kenya - Mutwiri, Antony; Dr Mareike Schomerus, (MUST Institutional Research Ethics Review Committee (MIRERC), 2025)
Executive Summary Behavioral experiments offer a unique lens of examining the intricate nature of the human decision making process and in recent years, behavioral insights have been used in the design and implementation of developmental programs. For 10 years now, Busara has applied the use of behavioral science across disciplines to test behaviorally informed solutions and advance its application in the Global South context including Kenya. The behavior change agenda across governments is most developed in the policy areas of environment, health, and transport (Darnton, 2008). Indeed, we cannot downplay the promising nature of the use of behavioral experiments in international development. By uncovering behavioral barriers and enablers to development outcomes, experimental studies offer actionable insights for designing more effective, targeted interventions that resonate with the preferences and motivations of beneficiaries. To bridge this gap, Busara is running a course on behavioral experiments in international development with students from the University of Chicago to help them unpack how experiments can be a powerful tool for good policy, what is necessary to consider when designing an experiment and to think through what makes a good policy recommendation. The students will be guided through the process of developing a research question, designing formative research instruments, contextualizing them to fit into the study context and analyzing the findings. Students will work in groups, on an experiment design that they will refine throughout the course as they go through the steps of understanding good research design (including considerations of what produces good evidence for policy), being ethical and inclusive, designing, conducting, and analyzing formative interviews, learning from formative research and identifying policy implications. As per tradition, Busara provides opportunities for students from local universities and junior staff within the organization to participate in similar courses. This course, offered by the University of Chicago, will follow the same approach. To enhance the learning experience, five local students will be recruited to collaborate with foreign students during the instrument and experimental design phases. This setup is designed to foster a shared learning experience, allowing students to engage, interact, and learn from one another. Over a 10-week period, students will progress through the course, with a key milestone in Week 5 requiring them to submit their group-developed formative research instruments on selected topics for data collection in Kenya. Before the data collection phase, these instruments will be submitted for ethics approvals by MIREC. For the rest of the course, students will analyze the insights gathered from the formative interviews to refine their experimental designs, culminating in final submissions of research designs in Week 10.